1996
DOI: 10.1097/00006534-199603000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Delay of the Denervation Process in Skeletal Muscle by Sensory Ganglion Graft and Its Clinical Application

Abstract: We examined the effects of dorsal root ganglion isografts on the denervation process of skeletal muscle. A segment of sciatic nerve was removed from each of 25 inbred Wistar-Kyoto rats. Fifteen were set aside as controls. In the remaining 10 rats, isogeneic cervical dorsal root ganglia were grafted to the severed distal stump of the common peroneal nerve. Between day 72 and day 286 postoperatively, both controls and recipients were killed after twitch and tetanic tension recording of the extensor digitorum lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…We and others have previously reported the beneficial effects of sensory-to-motor nerve repair, ''sensory protection'', [10][11][12][13][14][15][16][17][18][19][20][21] in preserving both distal nerve and muscle integrity and function. Sensory protection preserves muscle weight, histologic features, 20 and muscle function 21 following denervation.…”
mentioning
confidence: 99%
“…We and others have previously reported the beneficial effects of sensory-to-motor nerve repair, ''sensory protection'', [10][11][12][13][14][15][16][17][18][19][20][21] in preserving both distal nerve and muscle integrity and function. Sensory protection preserves muscle weight, histologic features, 20 and muscle function 21 following denervation.…”
mentioning
confidence: 99%
“…It was suggested that percentage values minimize variations between animals and are more useful than absolute values for comparisons among groups. [16][17][18] Analysis of variance (ANOVA) was used to evaluate differences between group means. A P value of 0.05 was accepted for statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that percentage values minimize variations between animals and are more useful than absolute values for comparison among groups. [16][17][18] Analysis of variance (ANOVA) was used to evaluate differences between group means. A P value of 0.05 was accepted for statistical significance.…”
Section: Discussionmentioning
confidence: 99%